Problematics of Muhammadiyah Learning at SMP Muhammadiyah 51 Sidikalang - Sinamo, Riswan; Pasaribu, Munawir (Edumaniora : Jurnal Pendidikan dan Humaniora, 2023)
The background of this research is that there are still problems in learning at SMP Muhammadiyah 51 Sidikalang regarding Kemuhammadiyahan lessons. Based on the results of observations made by researchers, one of the causes is the low interest in student learning in Kemuhammadiyahan lessons. This study aims to analyze the problems of student learning in the Kemuhammadiyahan subject, to reveal the constraints experienced by teachers and students and to explain the efforts made to overcome the obstacles that occur to the teachers and students. The method used in this research is descriptive using a qualitative approach. Respondents in this study are 2 people who have the criteria that have been explained. The data collection tools used in this study were observation sheets, interview sheets, and documentation. The results showed that the constraints experienced by the teacher were the lack of learning time and the lack of self-awareness of the students to better understand Muhammadiyah learning material. While the inhibiting factors of student learning interest are the lack of insight of the teacher when explaining learning to students to make it easier for students to understand the material taught by the subject teacher, the condition of the class is crowded, students have their own busyness when the teacher explains the material and students who are not ready to study in incomplete learning equipment. Efforts are being made to overcome the obstacles experienced by teachers and students by adding learning time so that students can calmly listen to the explanations taught by the teacher.